Rethinking the Socialist Intellectual in the British First New Left. Issue 5 (3rd September 2022) - Scott-Brown, Sophie
ABSTRACT: The first British New Left formed in response to a crisis in international and British socialism. Although never a formal movement, its associated members set themselves the tasks of, first, confronting the rapid change transforming social life at both global and national scales, and second, articulating a new political culture able to accommodate the good and resist the bad of it. As part of this process, a series of intense debates took place on the role of the socialist intellectual in stimulating such a culture. In this article, I consider three of the NL's main protagonists, EP Thompson, Stuart Hall, and Raphael Samuel, and the different positions they took on this issue. I argue here that while all made important contributions to the argument, Samuel's practice as an intellectual, currently the least well known of the three, is worth closer attention for its relevance to contemporary educational debates.